Clinical use of a hyperbaric chamber as a modality to aid in recovery - Hawkins, J.; Heumann, K. J. (Strength and Conditioning Journal, 2017)
The use of hyperbaric chambers has been tried by various athletes. Some professional athletes and physicians have reported phenomenal results with their regular usage. A review of the literature does not support the prevalent use of this modality however. Using a hyperbaric chamber to treat delayed-onset muscle soreness in particular has not been substantiated. Results are inconclusive with respect to treating postconcussion syndrome and fatigue. Additional data regarding these 2 treatments are needed.